The Pivotal Role of Mindfulness in Reducing the Stress of Teachers: A Quasi-Experimental Study - Mary Shaiby C. G.; Devaseelan S; Joseph Biju (The Bioscan, 2025)
Teacher stress is a growing concern in this technologically developed world as it negatively affects both professional performance and overall well-being. In this regard, Mindfulness-based interventions showed a greater impact in enhancing emotional regulation and reducing stress. This article aims at ‘the pivotal role of mindfulness in reducing stress’ by evaluating how a structured mindfulness program can reduce perceived stress levels among schoolteachers and increase their professional quality. The method used here is a quasi-experimental design in which both pre-test and post-test are done only on the experimental group to understand its impacts by observing the changes that occur in the participants (n=115) after the intervention program. The participants in the experimental group underwent a Mindfulness-Based Stress Reduction (MBSR) program for eight weeks. The questionnaires DASS-21 and FFMQ-15 are used as tools to collect data, and these data are analysed through the software program JASP 0.19.3. to obtain the results. The results showed that stress decreased by 73.9% (6.21 → 1.62), with a very high t-value (t = 13.078, p < 0.001), and mindfulness increased by 29.8% (47.84 → 62.11), with t = 22.556, p < 0.001. Moreover, the extremely large effect sizes (Cohen’s d ≈ 1.22 for stress, d ≈ 2.10 for mindfulness) demonstrate that the MBSR program is not only statistically significant but also a clinically sound program to reduce stress. These results place MBSR among the most effective psychological interventions for the reduction of occupational stress.